A TEXTBOOK ANALYSIS : AN IN-DEPTH ANALYSIS OF ACTIVITIES IN SCIENTIFIC APPROACH’S PERSPECTIVE IN AN EFL TEXTBOOK FOR SEVENTH GRADE - Ni’mal Fuyudloturromaniyyah (Journal of English and Education, 2015)
The need for teachers to analyze whether the textbook used applies learning approach demanded by the curriculum starts to raise. Therefore, this study aims to find out to what extent the activities given in the textbook follow the scientific approach in its design. This study belonged to descriptive evaluative method through content analysis. The main data were three chapters of the selected textbook. The texts were analyzed by using Task Analysis Sheet (TAS) adapted from Littlejohn (1998, in Tomlinson, 2011) rated by two experienced English teachers. The findings showed that in terms of physical appearence and types of activities the textbook was attractive since it is printed full color filled with pictures, illustration, various activities, songs, and games. However, the activities did not fully apply scientific approach as demanded by Curriculum 2013 since the five scientific learning activities were not evenly distributed. Questioning and Communicating activities existence were superior with 61% and 52% compared to Observing, Collecting information, and Associating ones with 22%, 14%, and 19% respectively.Therefore, considering the findings, it is suggested that the teachers should be always well prepared facing curriculum including the learning approach and textbooks changes by time goes by. Thus, they should be critical and creative once they found the lack of textbook provided by the government.